Behavioural correlates of stereotypic behaviour in Rhabdomys dilectus - Silber, Sarah (My University, 2018)
The specific causal mechanisms of stereotypies are difficult to establish, especially because they do not develop in all individuals of a species living in the same captive environment, and may be affected by other behaviours (e.g. personality) and the life history of the animal. The overarching aim of this study was to investigate the behavioural correlates of stereotypic behaviour in the striped mouse Rhabdomys dilectus, and to ascertain whether there are any specific traits associated with stereotypic behaviour in this species. I studied the behaviour of stereotypic and non-stereotypic striped mice in four behavioural assays, including: (1) general home cage behaviour; (2) dyadic encounters to assess social interactions; (3) personality tests to measure interindividual variation in behaviours; and (4) perseveration tests by means of a plus maze. Results indicated that: (1) stereotypic striped mice showed higher frequency and duration of active behaviour and higher rates of inactivity, whereas non-stereotypic mice displayed longer durations, but fewer occurrences, of inactivity; (2) social motivation was not a predictor of stereotypic behaviour in striped mice; (3) Stereotypic mice showed a proactive coping style typified by spending a longer time in the light compartment after a startle response, a greater manipulation of novel objects in the home cage, and increased activity levels in standard housing. Non-stereotypic mice showed a reactive coping style typified by greater anxiety and fear toward novel objects, and heightened inactivity; and (4) levels of perseveration were higher in stereotypic striped mice. I also found that stereotypic mice that showed higher frequencies and durations of activity also displayed a proactive coping style and were more preservative. In addition, non-stereotypic mice that were inactive for longer showed a reactive coping style and lower levels of perseveration, which suggests inactivity is a possible alternative response to stereotypy in captive environments. In conclusion, stereotypy, activity, personality, and coping style appear to have common underlying, possibly neurobiological, mechanisms. In particular, I hypothesise that dysfunction of the basal ganglia, or suppression of the indirect (striatopallidal) pathway, results in inappropriate repetitive responses and stereotypic behaviour. Further research is needed to measure brain hormones and structure in order to determine the nature of the imbalances and whether they are consistent within and between species. In addition, investigations are required of factors which may mediate these imbalances, including age of weaning and other genetic influences.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2018.
Keywords: Rhabdomys pumilio--Reproduction; Mice; Rhabdomys pumilio